An analytical geoinformation system for operational planning of the traffic routes of garbage trucks - Тевяшев, Андрей Дмитриевич; Матвиенко, Ольга Ивановна; Шиян, Олег Вадимович (Eastern-European Journal of Enterprise Technologies, 2015)
The article considers an effective approach to solve the problem of operational planning and monitoring of the traffic routes of garbage collectors in settlements on the basis of an analytical geoinformation system. The system structure is presented as three interrelated subsystems: geoinformation, analysis, and monitoring. We have suggested a mathematical formulation of the problem of effective planning of the traffic routes of garbage collectors and an efficient algorithm of solving it. The planned routes are controlled by the subsystem of monitoring vehicles that uses GPS-navigation. Implementation of the analytical geoinformation system for effective planning of the traffic routes of garbage trucks is an efficient means to improve environmental security as well as housing and utility energy and resource economy. Practical implementation of the devised plan of detailed routes for the removal of municipal solid waste allows reduction of the required number of garbage trucks (from three to two), cutting the total length of their routes, and decreasing by 35 % the actual fuel costs for the planned period of one month.